Reconstructing the Regulatory Framework for E-Government in Regional People’s Representative Councils to Enhance Public Aspiration Management - Widodo Widodo; Hafid Zakariya; Hanuring Ayu Ardhani Putri (Jurnal Ilmu Hukum Kyadiren, 2026)
The rapid expansion of infrastructure development through Indonesia’s Electronic Procurement Service (LPSE) has intensified the need for effective legal protection for construction service providers against local government default arising from delayed or unpaid contractual obligations. This study examines the legal framework governing contractor protection, analyzes the contractual liability of local governments as project owners, and evaluates the effectiveness of preventive and remedial legal protection mechanisms. Using an empirical legal research method with a socio-legal approach, the study investigates the implementation of legal protection in government construction procurement in Klaten Regency. The findings reveal that, despite a comprehensive legal framework incorporating the principles of equality and multiple dispute resolution mechanisms, implementation remains ineffective due to unequal bargaining power, inadequate payment guarantees, and limited use of the Dispute Board. Strengthening contractual safeguards, payment security, government accountability, and dispute resolution mechanisms is essential to ensure legal certainty and sustainable public procurement.